2021
DOI: 10.1016/j.pnpbp.2020.110137
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between neurological and cerebellar soft signs, and implicit motor learning in schizophrenia and bipolar disorder

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
1
12
0
1
Order By: Relevance
“…SZ individuals presented more severe deficits during SRTT when performing with their left hand. We have hypothesized that our findings could be associated with the structural and functional dysfunctions of the cerebellum and its networks, as observed in SZ and BD ( 5 7 ).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…SZ individuals presented more severe deficits during SRTT when performing with their left hand. We have hypothesized that our findings could be associated with the structural and functional dysfunctions of the cerebellum and its networks, as observed in SZ and BD ( 5 7 ).…”
Section: Introductionmentioning
confidence: 89%
“…No breaks were made between the blocks during the procedure. After finishing the task, participants were asked if they could identify the presence of the sequence, and if so, they were asked to recall it ( 5 7 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cerebellum is a preferential target of prions in Creutzfeldt–Jakob disease [ 78 ]. A growing number of studies indicate a significant role of this structure not only in motor coordination but also in regulation of emotions and cognition, particularly in executive functions [ 79 ], visuospatial functions [ 80 ], language [ 81 ] and memory [ 82 ] Moreover, it has been shown that the cerebellum may be related to the pathophysiology of bipolar disorder and schizophrenia, and the patients with those conditions present motor abnormalities related to the dysfunction of this structure [ 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. PrP c may play a role in the pathophysiology of mood disorders through its significant role in long-term depression (LTD), a critical cellular mechanism responsible for synaptic plasticity and neuroprotection against excitotoxicity in the cerebellum [ 91 , 92 ] Transgenic mice with knock-out of PrP c gene (Ngsk Prnp −/− ) presented impaired LTD in excitatory synaptic transmission at connections between parallel fibers and Purkinje cells.…”
Section: The Function Of the Prion Protein (Prp C ...mentioning
confidence: 99%
“…However, when opposed to the literature on schizophrenia, NSS in BD is a comparatively understudied area. Numerous studies, on the other hand, have discovered significant neurological and genetic similarities between schizophrenia and BD (Bora, 2016; Chrobak et al., 2021; Gotra et al., 2020). As a result, it's acceptable to assume that, similar to schizophrenia, several items in the NSS fit the requirements for a BD endophenotype.…”
Section: Introductionmentioning
confidence: 99%